PENGARUH MODEL PEMBELAJARAN KNISLEY TERHADAP KEMAMPUAN KONEKSI MATEMATIS SISWA KELAS VIII SMP NEGERI 7 MERANGIN - Nurhidayah; Ade Susanti (Mat-Edukasia, 2019)
The low ability of students' mathematical connections in SMP N 7 Merangin is one of the things underlying this research. There are three indicators of mathematical connection ability that cannot be mastered by students. Therefore, research using the Knisley learning model that aims to determine and describe the ability of mathematical connections using the Knisley learning model is better than using conventional learning in class VIII students of SMP N 7 Merangin. This type of research is experimental research with sampling using Simple Random Sampling. Data collection techniques through tests and data analysis techniques using t-test. From the results of the analysis obtained an average mathematical connection ability in the experimental class 34.96, while the control class obtained an average of 30.92. Hypothesis test results obtained, tcount = 2.1531 and ttable = 1.6814. Because tarithmetic > ttable then Ha is accepted. This study concludes that the ability of mathematical connections using the Knisley learning model is better than using conventional learning.